Professional development through teacher research: stories from language teacher educators - Fikri Yanda (IRecall Journal, 2024)
There is not enough information on the becoming and the professional development of language teacher educators as teachers of teachers. One way for teacher educator professional development is through teacher research. Here, teacher educators may not only enhance their practices immediately in their context but also assist in building transformative pedagogies in larger contexts by sharing their academic work. Professional Development through Teacher Research: Stories from Language Teacher Educators, edited by Darío Luis Banegas, Emily Edwards, and Luis S. Villacañas de Castro, seeks to comprehend how language teacher educators worldwide carry on developing professionally by investigating their personal teaching practices. The book aims to comprehend the benefits to students’ (future teachers) professional development that teacher educators see in undertaking research; to advance knowledge democratization by involving teacher educators from disadvantaged regions like Latin America and Africa; to investigate the motivations of language teacher educators in writing for publication; and to bridge the gap between educational practice and educational research in the programs of BA and MA in language education.